Paylater dalam Perspesktif Keuangan Islam: Analisis Prinsip Syariah terhadap Praktik Kredit Syariah : Paylater in the Perspective of Islamic Finance: An Analysis of Sharia Compliance in Digital Credit Practices - Herlinda Oktaviani; Abdul Ghofar Saifudin (Jurnal Keuangan dan Perbankan Syariah, 2026)
Purpose: This study aims to evaluate how well Paylater service methods align with Islamic finance's sharia rules. The study focuses on how contracts are structured, how interest or other fees are applied, late fees, and how these factors affect the values of benefit and justice in digital credit transactions that are emerging in the fintech era. Design/methodology/approach: This study employs a normative-descriptive research design and a qualitative methodology. Literature reviews on Islamic financial theories, Paylater procedures, fintech laws, and pertinent Sharia fatwas are the techniques employed. This method was selected in order to evaluate how well digital credit operations align with relevant Sharia rules and concepts.  Research Findings: The study's findings demonstrate that the majority of Paylater services continue to use traditional credit methods, which may involve aspects of injustice, gharar, and usury. Furthermore, the minimal restrictions and simplicity of usage of Paylater may promote excessive debt utilization and consumptive behavior, which would go against the Islamic banking principals of moderation and balance. Contribution/Originality/Novelty: This study's significance and originality are found in its thorough examination of Paylater as a contemporary digital credit phenomenon from the standpoint of Islamic finance. In addition to evaluating the contract's legal features, this study emphasizes its ethical implications and how it affects customer behavior. It also provides suggestions for creating a Sharia-based Paylater model that upholds Sharia values by encouraging justice, openness, and consumer protection.